2015
DOI: 10.1038/srep09818
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the causes of human illness due to consumption of azaspiracid contaminated shellfish

Abstract: Azaspiracid (AZA) poisoning was unknown until 1995 when shellfish harvested in Ireland caused illness manifesting by vomiting and diarrhoea. Further in vivo/vitro studies showed neurotoxicity linked with AZA exposure. However, the biological target of the toxin which will help explain such potent neurological activity is still unknown. A region of Irish coastline was selected and shellfish were sampled and tested for AZA using mass spectrometry. An outbreak was identified in 2010 and samples collected before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
1
23
2
Order By: Relevance
“…In neocortical neurons, voltage-gated sodium channels (VGSCs), N-methyl-d-aspartic acid (NMDA), glutamate receptors, and L-type Ca 2+ channels were not observed to play a role in AZA1-induced neurotoxicity, which is consistent with reports that AZA1 alone does not affect VGSC (Kulagina et al 2006;Twiner et al 2014). However, a recent study demonstrated that AZAs in the presence of glutaric acid (also found at significant concentrations in shellfish areas known for AZP events) inhibited sodium current through Na v 1.6 channels (Chevallier et al 2015) opening up the possibility that co-occurring secondary compounds may play a synergistic role in AZA toxicity. Nonetheless, AZAs have been shown to inhibit hERG (human ether-à-go-go-related gene) channels, a specific type of potassium ion channel (Twiner et al 2012a).…”
Section: Mechanisms Of Actionsupporting
confidence: 86%
“…In neocortical neurons, voltage-gated sodium channels (VGSCs), N-methyl-d-aspartic acid (NMDA), glutamate receptors, and L-type Ca 2+ channels were not observed to play a role in AZA1-induced neurotoxicity, which is consistent with reports that AZA1 alone does not affect VGSC (Kulagina et al 2006;Twiner et al 2014). However, a recent study demonstrated that AZAs in the presence of glutaric acid (also found at significant concentrations in shellfish areas known for AZP events) inhibited sodium current through Na v 1.6 channels (Chevallier et al 2015) opening up the possibility that co-occurring secondary compounds may play a synergistic role in AZA toxicity. Nonetheless, AZAs have been shown to inhibit hERG (human ether-à-go-go-related gene) channels, a specific type of potassium ion channel (Twiner et al 2012a).…”
Section: Mechanisms Of Actionsupporting
confidence: 86%
“…Recently, a toxic interaction between azaspiracid (50 nM) -a toxin found in shellfish harvested in Ireland -and GA (1 mM) was shown to produce a significant inhibition of sodium channels in in vitro experiments, while when added separately, these two compounds had no effects on these channels (Chevallier et al, 2015). Moreover, GA was found as a component of the same shellfish used in the study.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, they cause vomiting, nausea, diarrhoea and stomach cramps within a few hours after ingestion (Klontz, Abraham, Plakas, & Dickey, 2009) AZAs target several apoptotic modulators (Botana, et al, 2014;Roman, et al, 2002;Twiner, et al, 2005), such as caspase, cytoskeleton (Vilarino, Nicolaou, Frederick, Vieytes, & Botana, 2007), cytochrome release (Twiner, Hanagriff, Butler, Madhkoor, & Doucette, 2012), c-jun-N-terminal protein kinase (JNK), calcium levels (Cao, LePage, Frederick, Nicolaou, & Murray, 2010;Vale, Wandscheer, et al, 2008), fatty acid biosynthesis (Twiner, et al, 2008). AZAs decrease cell volume mediated by potassium and chloride efflux (Vale, Nicolaou, Frederick, Vieytes, & Botana, 2010), deplete ATP (Kellmann, et al, 2009), inhibit endocytosis (Bellocci, Sala, Callegari, & Rossini, 2010) and decrease procathepsin pools in endocytosis (Sala, Bellocci, Callegari, & Rossini, 2013) (Chevallier, et al, 2015), which could explain the neurotoxicity linked to AZA (Twiner, et al, 2014).…”
Section: Azaspiracid Groupmentioning
confidence: 99%